ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIKA SISWA SMP MENGGUNAKAN PEMBELAJARAN DARING BERBASIS GOOGLE MEET - Nika Fetria Trisnawati; Muhammad Fathurrahman; Diana Maria Basna (Program Studi PGSD Universitas Flores, 2022)
The implementation of learning from home requires teachers and schools to find alternatives to face-to-face learning with online learning. Of the several applications that can be used to support online learning, one of them is Google Meet. This study aims to analyze students' mathematical understanding abilities after doing online learning based on Google Meet. This study aims to analyze students' mathematical understanding abilities after doing online learning based on Google Meet. This research is a qualitative descriptive study that focuses on analyzing the ability to understand mathematics. The instruments used to collect data are test questions and questionnaires. The ability to understand mathematics is analyzed based on the concept of understanding according to Bloom's taxonomy, namely translation, interpretation, and extrapolation. From the results of the study, it was found that the highest level of student understanding was on the translation indicator and the lowest was on the extrapolation indicator with high-ability students having a good understanding of mathematics and students with low abilities not being able to understand mathematics learning given online.